Painting colourful prisons of power : a study of Chinese foreign manicurists in nail salons in Singapore. - Lim, Emmaline Zi Wei. (2011)
Power is understood to be a ubiquitous element that could be harnessed and perceived by different actors in different situational interactions. In this paper, my study is focused on the understanding and depicting the power of foreign Chinese manicurists within the premises of the salon. I would be exploring the strategies and tactics that these manicurists use to understand the ways that they incorporate different elements to achieve their aims. I would also like to show that beauty service work in the salon is not restricted to utilitarian terms but instead could be transformed into a domain of feminine power and interactions.